2021
DOI: 10.1007/s11524-021-00519-0
|View full text |Cite
|
Sign up to set email alerts
|

Correction to: Eviction, Health Inequity, and the Spread of COVID-19: Housing Policy as a Primary Pandemic Mitigation Strategy

Abstract: As a result of an error during the publication process, the middle initial of coauthor Danya E. Keene was incorrectly presented in this article as originally published as "A.". The original article has been corrected.Springer Nature regrets the error.Publisher's Note Springer Nature remains neutral with regard to jurisdictional claims in published maps and institutional affiliations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 0 publications
0
5
1
Order By: Relevance
“…of older adults, whose preferences differ from less vulnerable residents and are critical to addressing the impact COVID-19 had on well-being (Hartt 2020, Brüchert et al 2021, but also of differences across cantons, which have been shown to play a key role in the definition of housing and health policies (Glaser 2020, Rossini 2020. Moreover, the observed decrease in the desire for a place for 'sleeping, eating, working' evinces that in contrast to other studies (Cole et al 2020, Jones and Grigsby-Toussaint 2020, Tinson and Clair 2020, Benfer et al 2021, the survey did not exhaustively capture the effects of the pandemic for situations of homelessness, overcrowding, and poor quality or insecure housing. Secondly, the survey depicts preferences during a clearly delimited time frame; on the one hand, the observed changes might look different at the present time -one year into the pandemic, on the other hand, independent measurement of pre-pandemic preferences are not available for comparison.…”
Section: Limitationscontrasting
confidence: 74%
“…of older adults, whose preferences differ from less vulnerable residents and are critical to addressing the impact COVID-19 had on well-being (Hartt 2020, Brüchert et al 2021, but also of differences across cantons, which have been shown to play a key role in the definition of housing and health policies (Glaser 2020, Rossini 2020. Moreover, the observed decrease in the desire for a place for 'sleeping, eating, working' evinces that in contrast to other studies (Cole et al 2020, Jones and Grigsby-Toussaint 2020, Tinson and Clair 2020, Benfer et al 2021, the survey did not exhaustively capture the effects of the pandemic for situations of homelessness, overcrowding, and poor quality or insecure housing. Secondly, the survey depicts preferences during a clearly delimited time frame; on the one hand, the observed changes might look different at the present time -one year into the pandemic, on the other hand, independent measurement of pre-pandemic preferences are not available for comparison.…”
Section: Limitationscontrasting
confidence: 74%
“…Finally, both impacted and non‐impacted participant groups were able to adhere to safety, sanitation and social distancing measures, and had good access to reliable preventive COVID‐19 information via mass media, official public health sources and HF services. Some of the positive effects as well as non‐observed effects discussed previously could directly relate to the vital role of stable and safe housing paired with robust social and health support (Benfer et al, 2021 ; Mehdipanah, 2020 ) that participants received. In fact, participants had been receiving long‐term HF services, which included having a stable and safe house to live, access to continuous case management and multidisciplinary social and health supports (Hwang et al, 2012 ; Stergiopoulos et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…Finally, both impacted and non-impacted participant groups were able to adhere to safety, sanitation and social distancing measures, and had good access to reliable preventive COVID-19 information via mass media, official public health sources and HF services. Some of the positive effects as well as non-observed effects discussed previously could directly relate to the vital role of stable and safe housing paired with robust social and health support (Benfer et al, 2021;Mehdipanah, 2020) that participants received.…”
Section: Covid-19 Safety Measures and Access To Preventive Informationmentioning
confidence: 98%
“…It was assumed by local authorities that in addition to officially registered residents further not-registered persons lived in the RCs, in particular in RC2, therefore overcrowding was likely even more severe. Physical distancing, self-isolation, and shielding may be difficult to implement in these settings ( 2 , 15 , 16 ). The high genomic sequence similarity of a subset of samples from outbreak 2 supports the hypothesis that all cases belonged to the same outbreak and there is no evidence of multiple introductions.…”
Section: Discussionmentioning
confidence: 99%
“…The severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) is easily transmissible by both symptomatic and asymptomatic individuals. Closed and densely inhabited environments favor transmission (1)(2)(3).…”
Section: Introductionmentioning
confidence: 99%